Photo-controlled Conformation-assisted Permanent Optical Storage Device Employing a Polymer Network Liquid Crystal - Hegde, Gurumurthy; Jayalakshmi, Vallamkondu; Naira, Geetha Gopinathan; Prasad, Subbarao Krishna (Royal Society of Chemistry, 2009)
A new type of optical storage device is described employing a material consisting of a host nematic liquid crystal, a photoisomerisable azobenzene component and a photopolymerizable monomer. The principle of image storing involves selectively controlling the birefringence of the medium immediately prior to photopolymerization of the monomer. We show that photoisomerisation driven nematic to isotropic transition can be employed to achieve this through proper timing of the reverse isomerization of the azobenzene compound before the nematic director fluctuations get quenched. It is also suggested that grey-shades can be created in this device using the recently discovered phenomenon of electric-field acceleration of reverse isomerisation.